African Archaeology Without Frontiers Papers from the 2014 PanAfrican Archaeological Association Congress - Kusimba, Chapurukha M (Wits University Press, 2016)
Confronting national, linguistic and disciplinary boundaries, contributors to African Archaeology Without Frontiers argue against artificial limits and divisions created through the study of 'ages' that in reality overlap and cannot and should not be understood in isolation. Papers are drawn from the proceedings of the landmark 14th PanAfrican Archaeological Association Congress, held in Johannesburg in 2014, nearly seven decades after the conference planned for 1951 was re-located to Algiers for ideological reasons following the National Party's rise to power in South Africa. Contributions by keynote speakers Chapurukha Kusimba and Akin Ogundiran encourage African archaeologists to practise an archaeology that collaborates across many related fields of study to enrich our understanding of the past. The nine papers cover a broad geographical sweep by incorporating material on ongoing projects throughout the continent including South Africa, Botswana, Cameroon, Togo, Tanzania, Kenya and Nigeria. Thematically, the papers included in the volume address issues of identity and interaction, and the need to balance cultural heritage management and sustainable development derived from a continent racked by social inequalities and crippling poverty. Edited by three leading archaeologists, the collection covers many aspects of African archaeology, and a range of periods from the earliest hominins to the historical period. It will appeal to specialists and interested amateurs.